Faktor-faktor yang Mempengaruhi Niat Mahasiswa Mengikuti Kuliah Akuntansi dengan E-learning: Pendekatan Theory of Planned Behavior - Entot Suhartono; Alfia Nita Pratiwi (Universitas Dian Nuswantoro, 2023)
One of the impacts of the COVID-19 pandemic in Indonesia is the shift from face-to-face learning to online distance learning or e-learning. One educational institution that adopts this learning system is a college or university. The institution must provide an e-learning system based on LMS (Learning Management System) to help manage and organize the learning process, especially in Accounting. Improve the ability and understanding of accounting for students. This research aims to analyze student learning behaviour through LMS-based e-learning with the Theory of Planned Behavior approach. The research data is primary data obtained through questionnaires with Dian Nuswantoro University accounting study program students as respondents with a sample of 100 students. The data analysis method used in the study was SEM (Structural Equation Modeling) using the SmartPLS application. Exogenous variables include attitudes towards behaviour, subjective norms, and perceived behavioural control, while endogenous variables include behavioural interest and behaviour. The results of this research analysis are that attitude towards behaviour; and subjective norms significantly positively affect behavioural interest. Perceived behavioural control has no significant effect on behavioural interest. Behavioural interest significantly affects the behaviour of using or accepting LMS-based e-learning as an accounting learning tool.Keywords: attitudes toward behavior; subjective norms; perceived behavioral control; behavioral intention.